2004
DOI: 10.1007/s00192-004-1134-z
|View full text |Cite
|
Sign up to set email alerts
|

Tension-free vaginal tape, Burch, and slings: are there predictors for early postoperative voiding dysfunction?

Abstract: This study compared the incidence, duration, and predictors of early postoperative voiding dysfunction (VD) after three continence operations. Charts of women undergoing tension-free vaginal tape (TVT), Burch, or suburethral sling were reviewed. Early postoperative VD was defined as urinary retention or postvoid residual (PVR) >200 ml at discharge. Analysis of variance, Chi-square, and non-parametric tests were used. Sixty-three TVT, 42 Burch and 33 slings were identified. Incidence of VD with TVT, sling, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 22 publications
4
24
0
1
Order By: Relevance
“…While this work was limited by retrospective design, the fact that current practice trends are moving towards minimally invasive slings for management of USI, and the fact that only 28% of the study population underwent a minimally invasive sling procedure, the mean hospital length of stay (2.8 days) was comparable to that previously reported for in-patient urinary incontinence surgeries (2.7 days) [20]. The previously reported work on voiding before discharge after in-patient USI surgeries was a smaller series (n=138) and reported a longer average length of hospital stay (4 days) [16]. In the current study, 41.8% of women successfully voided before hospital discharge.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…While this work was limited by retrospective design, the fact that current practice trends are moving towards minimally invasive slings for management of USI, and the fact that only 28% of the study population underwent a minimally invasive sling procedure, the mean hospital length of stay (2.8 days) was comparable to that previously reported for in-patient urinary incontinence surgeries (2.7 days) [20]. The previously reported work on voiding before discharge after in-patient USI surgeries was a smaller series (n=138) and reported a longer average length of hospital stay (4 days) [16]. In the current study, 41.8% of women successfully voided before hospital discharge.…”
Section: Discussionsupporting
confidence: 60%
“…Uroflow rates, postvoid residual volume, the presence of detrusor contraction at time of preoperative voiding study, the need for suprapubic catheter at time of discharge, and total number of days of catheterization have been associated with need to catheterize postoperatively [11][12][13][14][15][16][17][18][19]. Given this variation in reported associated variables, challenges exist when attempting to adequately counsel individual women regarding their likelihood of voiding success after USI surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a report of 205 TOT and 213 TVT, Barber et al (12) found high preoperative PVR to be a consistent risk factor for prolonged postoperative catheterization and slow resumption to normal voiding. In contrast, Minassian et al (19) retrospectively analyzed 138 patients who underwent antiincontinence surgery, including TVT, Burch or pubovaginal slings and found that patients with early postoperative VD (defined as a residual of >200 ml at discharge) had lower preoperative PVRs than those who did not (50 vs. 75 ml). Barron et al (20) reported that a Valsalva leak point pressure of more than 60 cm H 2 O and a maximum urethral closure pressure of more than 20 cm H 2 O were associated with a successful immediate voiding trial.…”
Section: Urodynamic Parametersmentioning
confidence: 99%
“…[9][10][11][12] Interrupted voiding and slightly elevated postvoid residuals may be considered normal. [10][11][12] However, if the obstructive sling is left untreated it may result in recurrent urinary tract infections, hypotonic bladder, and detrussor overactivity. 13 Since our practice is composed primarily of referrals after procedure failures, we sought a technique to further loosen or cut the sling in the office if voiding dysfunction or retention developed.…”
Section: Introductionmentioning
confidence: 98%